1992
DOI: 10.3382/ps.0710894
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Turkey Poults to Virginiamycin as Influenced by Litter Condition and Experimentally Induced Stunting Syndrome

Abstract: Two experiments were conducted to evaluate the effect of virginiamycin (VM, 22 mg/kg of diet) on performance of uninfected (CON) turkey poults and those infected (INO) with stunting syndrome and reared on used woodshavings (Experiment 1) or on clean or used woodshavings (Experiment 2). Virginiamycin improved BW (P less than .001) and feed efficiency (FE) (P less than .05) from 1 to 29 days of age, irrespective of type of litter or disease condition. The increase in BW induced by VM, however, was greatest when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Inoculation of turkey poults with an SS inoculum depressed weight gain (P < 0.001) and impaired the utilization of feed per gain (P < 0.001) up to 9 d (Angel et al, 1990a) and 14 d (Angel et al, 1990b) of age. However, Angel et al (1992) also found that feeding a complex diet containing fish meal and sunflower meal as the main protein sources eliminated the adverse effects of SS inoculation on performance traits compared with SS effects on poults fed a corn and soybean meal diet. This observation demonstrated the potential dietary effect on the manifestation of an enteric disease.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Inoculation of turkey poults with an SS inoculum depressed weight gain (P < 0.001) and impaired the utilization of feed per gain (P < 0.001) up to 9 d (Angel et al, 1990a) and 14 d (Angel et al, 1990b) of age. However, Angel et al (1992) also found that feeding a complex diet containing fish meal and sunflower meal as the main protein sources eliminated the adverse effects of SS inoculation on performance traits compared with SS effects on poults fed a corn and soybean meal diet. This observation demonstrated the potential dietary effect on the manifestation of an enteric disease.…”
Section: Introductionmentioning
confidence: 95%
“…Even though dietary supplementation of antibiotics and other additives may favorably alter gut microflora and reduce mortality due to enteric disease, they have little effect on alleviating the stunted growth of those birds surviving an enteric disease (Al-Batshan et al, 1992), including PEMS (Ferket, 1995). Irreparable damage to the gut often occurs during enteric disease.…”
Section: Introductionmentioning
confidence: 99%